Proposing and designing a new revocation protocol in VANETs - Mennad, Hadj Ahmed; Begouga, Nadhir; Chaïb, Noureddine (Université Amar Telidji - Laghouat - Département d'informatique, 2021)
Vehicular Ad Hoc Networks (VANETs) allow sharing different kinds of data between vehicles in a collaborative way. which aim enhancement of traffic safety and security by exchanging data in a safe manner to both drivers and passengers.These networks have become vulnerable to attackers who can launch attacks that can cause great damage or even threaten the life and safety of people. For that a large body of work has emerged during recent years, proposing the use of revocation techniques which can satisfy security requirements. In this thesis, we will learn more about the vehicular networks. Then we will see the various security challenges, some of the major attacks that may be faced and detection and revocation techniques of malicious nodes. We will provide an approach to improving existing security solutions and ensuring a high quality of service.The performance will be evaluated according to the simulation results which show the efficiency of our solution.